2013
DOI: 10.1002/adfm.201203705
|View full text |Cite
|
Sign up to set email alerts
|

Bright White Scattering from Protein Spheres in Color Changing, Flexible Cuttlefish Skin

Abstract: Throughout nature, elegant biophotonic structures have evolved into sophisticated arrangements of pigments and structural reflectors that manipulate light in the skin, cuticles, feathers and fur of animals. Not many spherical biophotonic structures are known and those described are often angle dependent or spectrally tuned. White light scattering by the flexible skin of cuttlefish (Sepia officinalis) is examined and how the unique structure and composition of leucophore cells serve as physiologically passive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
100
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 42 publications
5
100
0
Order By: Relevance
“…We speculate that differences in gene expression and the resulting protein composition (potentially including the unidentified major protein bands and the unique relative ratios of the known reflectins we observe in electropherograms of the leucophore tissue) help direct the morphology of the high-index material controlling the optical properties of these otherwise similar cells. We suggest that it is this mesoscale assembly of the variety of reflectin protein subtypes (and their associated membrane structures) found throughout cephalopods that differentially creates distinct sub-cellular structures with specific optical properties ranging from specular to diffuse reflectance (Holt et al, 2011;Sutherland et al, 2008), from static to adaptive reflectance Kramer et al, 2007;Tao et al, 2010) and from narrowband to broadband reflectance (Mäthger et al, 2009;Mäthger et al, 2013), with colors tunable from red to blue and from transparent to highly reflective (Ghoshal et al, 2013;Kramer et al, 2007). This multitude of reflectin-based structures and their photonic properties is increasingly recognized as an interesting model of mesoscale assembly and its control for the design of functional materials.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We speculate that differences in gene expression and the resulting protein composition (potentially including the unidentified major protein bands and the unique relative ratios of the known reflectins we observe in electropherograms of the leucophore tissue) help direct the morphology of the high-index material controlling the optical properties of these otherwise similar cells. We suggest that it is this mesoscale assembly of the variety of reflectin protein subtypes (and their associated membrane structures) found throughout cephalopods that differentially creates distinct sub-cellular structures with specific optical properties ranging from specular to diffuse reflectance (Holt et al, 2011;Sutherland et al, 2008), from static to adaptive reflectance Kramer et al, 2007;Tao et al, 2010) and from narrowband to broadband reflectance (Mäthger et al, 2009;Mäthger et al, 2013), with colors tunable from red to blue and from transparent to highly reflective (Ghoshal et al, 2013;Kramer et al, 2007). This multitude of reflectin-based structures and their photonic properties is increasingly recognized as an interesting model of mesoscale assembly and its control for the design of functional materials.…”
Section: Discussionmentioning
confidence: 96%
“…To date, there have been no reported adaptive (i.e. tunable) leucophores (Mäthger et al, 2009;Mäthger et al, 2013). Among the many biological materials functioning specifically for broadband scattering, there are only a few documented examples of reversible broadband scattering structures in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding that granules contain significant amounts of the high-refractive-index protein reflectin is important because rsif.royalsocietypublishing.org J. R. Soc. Interface 11: 20130942 reflectins are associated with the production of structural coloration in cephalopod iridophores [15,29,30] and leucophores [10]. For the first time, these proteins have been found in a cephalopod chromatophore, which has classically been deemed a pigmentary organ.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3] In nature, bright white appearance arises from the dense arrays of pterin pigments in pierid butterflies, [4] guanine crystals in spiders, [5] or leucophore cells in the flexible skin of cuttlefish. [6] A striking example of such whiteness is found in the chitinous networks of white beetles, e.g., Lepidiota stigma and Cyphochilus sp. [7][8][9] Previous research investigating these beetle structures has shown that the chitinous network is one of the most strongly scattering materials in nature, and therefore the question arises whether this structure is evolutionary optimized for strong scattering while minimizing the Most studies of structural color in nature concern periodic arrays, which through the interference of light create color.…”
mentioning
confidence: 99%